VALIDATION OF HIV VIRAL LOAD Bioneer AccuPower® HIV-1 Quantitative RT-PCR Kit Compare to Roche-Cobas®4800 System HIV-1 - Maskito, Veronika Juanita; Kosasih, Agus Susanto; Sugiarto, Christine (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
The Bioneer AccuPower®HIV-1 Quantitative renewed the LoD from 38 IU/mL to 33 IU/mL. Performance evaluation of the kit has not been carried out in Indonesia since the alteration, as it is expected that the new kit will have improved sensitivity. This study is a cross-sectional evaluation of the correlation, sensitivity, and specificity of the Bioneer-AccuPower HIV Quantitative RT-PCR Kit compared to the Roche-Cobas 4800 System HIV-1. We obtained venous EDTA plasma from 211 HIV patients tested in the Clinical Pathology Laboratory of Dharmais Hospital, Indonesia. Subject werw  71 high-viral-load samples (>1000 copies/mL), 60 low-viral-load samples (<1000 copies/mL), and 80 undetectable-viral-load samples (<14.2 copies/mL/<24.42 IU/mL). Exclusion criteria were samples under the limit of quantification of each instrument (Roche-Cobas®4800 20 copies/mL (34.4 IU/mL); Bioneer-AccuPower 69.4 copies/mL (49.97 IU/mL)). Ethical Declaration released by Dharmais Hospital Ethical Committee No.DP.04.03/11.7/0872024. The categorical contingency correlation in determining whether the HIV viral load sample was high, low, or undetectable was 0.863. The sensitivity, specificity, and accuracy of the Bioneer-AccuPower HIV Quantitative RT-PCR Kit, compared to the Roche Cobas 4800 System HIV-1, in quantifying HIV viral load were 99.15%, 96.25%, and 98.10%, respectively. Regarding the limit of quantification of each instrument, the Bioneer-AccuPower HIV Quantitative RT-PCR Kit performed well in determining HIV RNA viral loads, making it suitable for HIV screening. It exhibits a strong correlation compared to the Roche Cobas® 4800 System HIV-1. However, it required a larger study that did not limit the sample according to the limit of quantification of both instruments and sequenced the discrepancy samples.